TANGGAPAN PENGUNJUNG TENTANG FASILITAS STREET FURNITURES DI KAWASAN WISATA HAPANASA KABUPATEN ROKAN HULU - Arief, Andi M. Rifiyan; Ma’aruf, Zainal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Street Furnitures facilities is very important for a tourist attraction, which is to fulfill the wishes of visitors so that visitors feel comfortable and happy while in the tourist attraction, so as to increase tourist arrivals in the tourist attraction. The reseacrh aims to determine tourist responses in The Hot Water Hapanasan Rokan Hulu Riau Province. This study used a descriptive quantitative method to examine problems in the lift. The samples in this study were 5 respondents, who were taken by using accidental sampling. While data collection techniques in this study using observation, questioner, and interviews. By using a Likert scale as a measure to determine the length of the short interval. With sub-variables on street furnitures (Wardiyanto and Baiquni, 2011) is divided into Parking Area, Street Light and Pedestrian, Trash Can, Attraction List, Map and Information, Bench and Public Toilet. From the results of research conducted in the field of research on the tourist responses in Hot Water Hapanasan Rokan Hulu Riau Province in the category still lacking from good.Keywords : Street Furnitures,Parking Area, Street Light and Pedestrian, Trash Can, Attraction List, Map and Information, Bench and Public Toilet.